MAKNA BAHASA TUBUH: SUATU KAJIAN LINTAS BUDAYA - Mileh I Nengah (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
This study is entitled "The Meaning of Body Language: A Cross-Cultural Study". In expressing thoughts and feelings through language uses words as a means. In addition, there are also languages that do not use words as a means of expression, this kind of language is called body language. Body language uses body movements as a means of expression. This study aims to find similarities and differences in body language from two countries, namely Indonesia and Japan. Observation methods and note techniques are used in data collection, descriptive methods are used to analyze data assisted by inductive or deductive techniques, while the presentation of the results of the analysis is using informal and formal methods. This study found several similarities and differences in the meaning of body language from two different countries, namely Indonesia and Japan.